Senegal assessment [of the PEDAL project] - Resnick, Danielle; Diatta, Ampa Dogui (International Food Policy Research Institute, 2025)
For nearly three decades, Senegal has been recognized as a regional leader in advancing nutrition, reducing under-five stunting from 34 percent in 1992 to 19 percent in 2014 (Kampman et al. 2017), and further to 15.1 percent by 2023 (ANSD and ICF 2024). This progress has been underpinned by a multi-sectoral and decentralized approach, with local governments playing an increasingly central role in policy implementation. Large-scale food fortification (LSFF) has been a cornerstone of this agenda, with Senegal—alongside Nigeria—pioneering fortification standards in the 2000s for edible oil, wheat flour, and salt, and subsequently institutionalizing the approach through the 2006 Strategic Plan for the Fortification of Foods and two successive national fortification strategies, the most recent of which was launched in May 2025. Yet despite these achievements, Senegal now faces mounting fiscal pressures, shifting donor priori-ties, and persistent micronutrient challenges, all of which threaten to slow or reverse momentum around LSFF.